EXPLORING PERSONALITY PATHOLOGY: A PERSON-CENTERED APPROACH TO THE DSM-5’S ALTERNATIVE MODEL OF PERSONALITY DISORDERS - Heuckeroth, Sarah Ann (Wake Forest University, 2018)
The purpose of this paper is to investigate the gap between the two models of personality pathology in the DSM-5 and to attempt to bridge this gap. These models are the traditional categorical personality disorder model and the proposed alternative dimensional model. Based on this purpose, a person centered analysis approach was applied to the Criterion B traits of the alternative dimensional model to explore whether these pathological personality traits define distinct diagnostic categories. This work is important because it contributes to the search for the elusive “optimal approach for diagnosing a personality disorder” (Hallquist & Wright, 2014, p. 6). Clarifying the conceptualizations of personality pathology has the potential to increase understanding of these disorders and facilitate treatment for patients with personality pathology. It may also contribute to the implementation of the DSM-5’s alternative personality disorder model in the future. The current project consists of two studies. The first study analyses online self-report data on the pathological personality traits. The second study analyses an archival data set that contains both self-reported and clinician-rated levels of the pathological personality traits. Both studies use latent profile analysis (LPA) to explore the existence of categorical latent groups defined by these traits. I also looked for categories both within the whole sample, and within a high pathology sub-sample in the two studies. In general, the results showed quantitative differences in personality pathology rather than qualitative. The group recovered from the LPA reflected different mean levels of pathology overall, not distinct patterns. This suggests that personality pathology may be best conceptualized dimensionally.
Keywords: Latent Profile Analysis; Pathology; Personality; Personality Disorders; Personality Pathology